Detection of Mycobacterium ulcerans in the environment predicts prevalence of Buruli ulcer in Benin. - Heather R Williamson; Mark E Benbow; Lindsay P Campbell; Christian R Johnson; Ghislain Sopoh; Yves Barogui; Richard W Merritt; Pamela L C Small (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: Mycobacterium ulcerans is the causative agent of Buruli ulcer (BU). In West Africa there is an association between BU and residence in low-lying rural villages where aquatic sources are plentiful. Infection occurs through unknown environmental exposure; human-to-human infection is rare. Molecular evidence for M. ulcerans in environmental samples is well documented, but the association of M. ulcerans in the environment with Buruli ulcer has not been studied in West Africa in an area with accurate case data. METHODOLOGY/PRINCIPAL FINDING: Environmental samples were collected from twenty-five villages in three communes of Benin. Sites sampled included 12 BU endemic villages within the Ouheme and Couffo River drainages and 13 villages near the Mono River and along the coast or ridge where BU has never been identified. Triplicate water filtrand samples from major water sources and samples from three dominant aquatic plant species were collected. Detection of M. ulcerans was based on quantitative polymerase chain reaction. Results show a significant association between M. ulcerans in environmental samples and Buruli ulcer cases in a village (p = 0.0001). A "dose response" was observed in that increasing numbers of M. ulceran- positive environmental samples were associated with increasing prevalence of BU cases (R(2) = 0.586). CONCLUSIONS/SIGNIFICANCE: This study provides the first spatial data on the overlap of M. ulcerans in the environment and BU cases in Benin where case data are based on active surveillance. The study also provides the first evidence on M. ulcerans in well-defined non-endemic sites. Most environmental pathogens are more broadly distributed in the environment than in human populations. The congruence of M. ulcerans in the environment and human infection raises the possibility that humans play a role in the ecology of M. ulcerans. Methods developed could be useful for identifying new areas where humans may be at high risk for BU.